Fun At Work dari Sudut Pandang Aparatur Sipil Negara (ASN): Studi Kualitatif pada Instansi Pemerintahan di Indonesia - Wibawa, Febrian; Sari, Nayunda Andhika (UI Scholars Hub, 2025)
The concept of fun at work is often discussed in various studies as an activity that supports a positive work climate and provides a variety of positive experiences for employees. However, there is debate in seeing the impact of implementing fun at work in the workplace, especially in the context of public services. To date, research related to fun at work in the context of public services or government institutions is still very limited. By focusing on the civil servants or ASNs in Indonesia, this study aims to explore the perceptions and experiences of fun at work for ASNs. This research was conducted with a qualitative study of 12 ASNs from one of the public service offices in the Jakarta area using a semi-structured in-depth interview method. Analysis of the results shows that fun at work is perceived variously, namely as a 'double-edged sword', an identity balancer, and a medium for egalitarian and family relatedness. This research contributes empirically in enriching the meaning of fun at work in the context of public services and ASN in Indonesia. The results of this study can be used as a reference for organizations in the public sector in implementing various policies that can support a positive work climate.